2014
DOI: 10.6061/clinics/2014(09)08
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin can downregulate the levels of inflammatory mediators in the hippocampus of rats submitted to pilocarpine-induced status epilepticus

Abstract: OBJECTIVE:Refractory status epilepticus is one of the most life-threatening neurological emergencies and is characterized by high morbidity and mortality. Additionally, the use of anti-inflammatory drugs during this period is very controversial. Thus, this study has been designed to analyze the effect of a low dose of indomethacin (a COX inhibitor) on the expression of inflammatory molecules.METHOD:The hippocampus of rats submitted to pilocarpine-induced long-lasting status epilepticus was analyzed to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
(29 reference statements)
4
4
0
Order By: Relevance
“…We showed that PILO rats displayed increased expression of major inflammatory cytokines, as reported in different epileptic models (De Simoni et al, 2000;Vieira et al, 2014;Voutsinos-Porche et al, 2004 (Martin et al, 2003;Patel et al, 2016). -Sarmiento et al, 2015;Gendron et al, 2004;Vita et al, 1998).…”
Section: Ntsr2 Is Induced In Reactive Astrocytes and Microglial Cells In Vitro Following Proinflammatory Stimulationsupporting
confidence: 76%
“…We showed that PILO rats displayed increased expression of major inflammatory cytokines, as reported in different epileptic models (De Simoni et al, 2000;Vieira et al, 2014;Voutsinos-Porche et al, 2004 (Martin et al, 2003;Patel et al, 2016). -Sarmiento et al, 2015;Gendron et al, 2004;Vita et al, 1998).…”
Section: Ntsr2 Is Induced In Reactive Astrocytes and Microglial Cells In Vitro Following Proinflammatory Stimulationsupporting
confidence: 76%
“…3 ). This result is similar to the data obtained using the pilocarpine-induced model of epilepsy, wherein indomethacin administration prior to pilocarpine injection downregulates the expression of IL-1β in rats [ 33 ]. In addition, we showed that indomethacin significantly downregulated the mRNA expression of cox2b , but only at a concentration of 307 μM.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with this, increased PGE 2 production and IL-6 levels in IL-1β-stimulated human fibroblast-like synoviocytes from patients with disk displacement were reversed on in vitro treatment with COX-2 inhibitors, celecoxib, and indomethacin [73]. Indomethacin also reduced IL-1β and TNF-α expression in hippocampus of pilocarpine-induced SE rat model [74] demonstrating a regulatory effect of COX-2 on these inflammatory molecules. COX-2, therefore, acts as a central signaling molecule for various inflammatory processes and could be explored as a potential therapeutic target for the management of numerous diseases including epilepsy.…”
Section: Introductionmentioning
confidence: 71%
“…2a). Simultaneously, COX-2 inhibitors suppress the production of pro-inflammatory cytokines reducing inflammation [7274].
Fig.
…”
Section: Introductionmentioning
confidence: 99%